Evaluation of Polymer Modified Mortar and Bonding Agent for Structural Repair - Ojha, P N; Kaura, Puneet; Singh, Brijesh; Daniel, Y N; Kumar, Nitesh (Journal of Asian Concrete Federation, 2021)
olymer modified mortar is found to be suitable for structural repair and strengthening of damage structural elements. Conventional mortar is not preferred in repair of concrete since it has inferior mechanical property and durability performance. Polymer based mortar is an alternative to conventional mortar with enhanced mechanical properties. However, there are limited specifications and guidelines available for specifying PMM mixes for structural repair work. The research work aims to evaluate the mechanical performance of polymer based mortar with varying concentration of styrene butadiene rubber latex at laboratory scale. Another aspect in repair of corrosion damage structures is the bond between the substrate concrete and repair mortar. In order to study the effectiveness of bonding agents, the performance evaluation of bonding agents has been evaluated using slant shear test and pull-off test as per ASTM C 882 and EN 1542 respectively. Findings of study indicates that at 8-10 percent concentration of dry polymer solid by cement mass in polymer based mortar is the optimum dosage. Styrene-butadiene rubber based polymer mortar showed improvement in flow in comparison to normal mortar however, mixes with crushed sand shows decrease in flow which is due to presence of more fines. Slant shear and pull-off test method shows epoxy bonding agent give better bond strength as compared to SBR latex.